2020
DOI: 10.14202/vetworld.2020.2416-2421
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of pelvic fractures in dogs and cats in Algiers: Incidence and long-term clinical outcomes

Abstract: Aim: We performed a retrospective study to evaluate clinical complications and outcomes associated with non-operative management of pelvic fractures in dogs and cats and described owner satisfaction. Materials and Methods: Based on radiographic findings and fracture location, case records were classified into two groups. Group 1 included animals with acetabulum involvement that underwent conservative treatment plus femoral head-and-neck excision. Group 2 included animals without acetabulum involvement that un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The incidence of acetabular fractures varies between 14% and 43% (Hardie et al, 1999;Boswell et al, 2001;Mesquita et al 2009). Bouabdallah et al (2020) reported the incidence of acetabulum and pubis fractures to be 21.4% in their study. In our study, these rates are 11.3% and 12.6%, respectively.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The incidence of acetabular fractures varies between 14% and 43% (Hardie et al, 1999;Boswell et al, 2001;Mesquita et al 2009). Bouabdallah et al (2020) reported the incidence of acetabulum and pubis fractures to be 21.4% in their study. In our study, these rates are 11.3% and 12.6%, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…DeCamp (2005) stated that the most common fracture is the ilium fracture. Furthermore, Bouabdallah et al, (2020) reported in their study that the rate of ilium fractures among pelvic fractures was 35.7%. In the present study, we found that the rate of ilium fractures among pelvic fractures was 20.8%.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations